Marlowe's sacred city and the walls in The Jew of Malta. Issue 1 (April 2020) - Kim, Jaecheol
This essay surveys the juridical and biopolitical significance of the city walls in Christopher Marlowe's The Jew of Malta. Early modern cities were designed to control the spread of diseases, and the city space embodied discipline and governmentality. The function of Malta's walls is to protect the corpus politicum against pathogens, marking the distinction between physis and nomos . Marlowe defines this function by representing lives without: the national body is conceived as a living organism threatened by alien bodies. In the play's medicinal rhetoric, pathogenic infiltrations of Turks and Catholics are destroyed by another invasive body, a Jew.